Procedures in English - Vietnamese translation of book titles = Phương thức chuyển ngữ tiêu đề sách từ Tiếng Anh sang Tiếng Việt - Lê, Thị Thu Hòa (2021)
In recent years, there has been a rapid development of book translation in Vietnam. Translated books have been making up a huge percent in book market of Vietnam. In addition to book’s content translation, title forces translators to pay attention to. Despite the importance of book title translation, it has received little attention of Vietnamese researchers. Hence, this research investigated “Procedures in English-Vietnamese book title translation” to identify the application of procedures in translating children book titles. The study deployed 109 English children book titles and their Vietnamese versions, belonging to three publishers namely, Kim Dong Publishing House, Tre Publishing House and Nha Nam Publishing House from 2013 to 2014. Data of the study was collected, classified and displayed in form of percentage to indicate the most dominant procedure used in title translation. Besides, interviews with experienced translators were conducted with the aim of finding some recommendations on book title translation. One the basis of research’s results, it could come to a conclusion that among six procedures adopted by three publishers, couplets and literal translation were the most commonly used procedures applied in translating proper name titles and non-proper name titles respectively. The research also suggested that there were some exceptions when none of procedure was used to translate English titles. Moreover, the study gave useful suggestions for book translators when transferring the messages from one language into another.